Analisis Makna Pesan Iklan Layanan Masyarakat Uber Versi Boxes – Ayo Kita Unlocked Jakarta - Hanz Kristian Agung (TUTURRUPA, 2019)
Uber is one of the largest online transportation services in the world. In Indonesia alone Uber had time to try to operate before finally acquired by other transportation services. The object of this research is Youtube Uber advertising version Ayo Kita Unlockedjakarta. Uber Ads version Ayo Kita Unlockedjakarta represents the true condition of a metropolitan city full of private vehicles by office workers. This can be seen from the analysis of scenes per scene. This research uses qualitative descriptive method, content analysis, and semiotics approach Roland Barthes. The purpose of research conducted is to find out the meaning of the message to be conveyed by Uber advertisement version of Ayo Kita Unlockedjakarta. And the results of this research indicate the denotative and connotative meaning of this advertisement which makes it possible to reveal the meaning of the message that the advertisement shows the possibility of street condition occurring in metropolitan city especially Jakarta in case of congestion, if everyone is not aware to use public transportation service and more concerned with prestige and life is instantaneous.